Penerapan Pengaturan Trading In Influence Dalam Pembaruan Undang-Undang Tindak Pidana Korupsi - Yolanda Islamy (Nagari Law Review, 2020)
Since the reforms, cases of corruption and abuse of power still occur frequently. Corruption is categorized as an extraordinary crime. This is the background for the birth of UNCAC. As a country that has ratified UNCAC, Indonesia has not yet adopted the trading in influence arrangement in its positive law. In fact, if examined, there are several cases that clearly have an influence trading dimension but are often equated with bribery. Therefore, the writer in this study discusses the difference between bribery and trading in influence in eradicating criminal acts of corruption, as well as the urgency of applying the rule of trading in influence in reforming the criminal acts of corruption in Indonesia. This paper uses normative juridical methods in its study and is supported by secondary data in the form of primary, secondary and tertiary legal materials. The analysis used is qualitative analysis. The results of the study revealed that the trading in influence often has a similarity to bribery. However, there are fundamental differences between trading in influence with bribery, including: differences in the form of good deeds of trilateral relationship / bilateral relationship, legal subjects, forms of actions relating to authority or forms of acceptance of the two acts. The adoption of the provisions of trading in influence into Indonesia's positive law becomes an important urgency, although Indonesia has set its own provisions in the Draft Criminal Code, but these provisions still have weaknesses and do not accommodate all the provisions contained in UNCAC. Efforts to apply trading in influence can be made with the renewal of the Corruption Eradication Act.